Police Officers’ perspectives on state (police) violence: a sociomoral and psychological-driven study on disengagement - Soares, Mónica (2018)
This paper comprises a theoretical and empirical incursion into the phenomenon of state violence, namely police violence. Although extensively explored in different perspectives within and outside academia, police violence is complex and has not been sufficiently problematized yet. In our understanding, this phenomenon requires a dialectical and dynamic discussion wherein both the development of state powers (macro-perspective) and how these powers affect the subjectification of those who act on their behalf (micro-perspective) are articulated into a critical analysis. In more concrete terms, the present study contributes to such analysis by shedding light on the main processes of moral disengagement (cf. Bandura, 1990, 1999, 2004) disclosed in the internal perspectives of six Portuguese police officers about common daily work-related situations. To legitimize the resort to police violence, police officers rely heavily on different mechanisms of moral disengagement. For instance, sanitizing language (anchored in a police technical jargon) is typically used as a linguistic mechanism to disguise violent actions; advantageous comparisons with other law enforcement agencies or with the recipient’s conduct are typically employed; non-lethal violence is usually minimized and portrayed as innocuous; and the recipient of violence is usually dehumanised and seen as responsible for the acts of violence. The findings are discussed based on the moral disengagement theory (Bandura, 1990, 1999, 2004); on the denial approach (Cohen, 2001, 2003); and on the impact of organizational, legal and socio-cultural dimensions of police organization (e.g., Fassin, 2011; Huggins, Haritos-Fatouros, & Zimbardo, 2002).